Isolamento, caracterização e eficiência simbiótica de bactérias fixadoras de nitrogênio isoladas de Estilosantes (Stylosanthes ssp.) - Chaves, Josimar da Silva (2014)
Among potentially important forage legumes for edaphoclimatic conditions in Brazil, the genus Stylosanthes appears as alternative for improving the soil fertility in consortium with grasses, both by the adaptation to the system as well as the ability to establish symbiosis with nitrogen-fixing bacteria. The aim of this study was isolate, characterize and assess the biological nitrogen fixation efficiency of the bacterial isolated from nodules of Stylosanthes ssp. Samplings of Stylosanthes ssp. plants were taken from two municipalities of Roraima State (Boa Vista and Bonfim), and plant’s exsiccates were sent for botanical identification at Integrated Museum of Roraima. The plant’s roots were washed with water and a total of 564 nodules were collected and isolated on YMA medium. Additionally, 34 isolates previously obtained from Stylosanthes sp. were also included in the study. After purification, the isolates were morphologically characterized, considering the time to growth, culture medium pH reaction, shape and aspect of the colonies and mucus. A clustering analysis was further performed with the Jaccard index. An authentication experiment was carried on during 20 days in glasshouse with 89 isolates inoculated in cowpea. The isolates were selected based on morphological groups and also Stylosanthes species that they had been isolated. Forty-four isolates that nodulated cowpea were after used for symbiotic efficiency evaluation in Stylosanthes capitata (cv. Lavradeiro). This experiment was performed in glasshouse where it was used the strain BR 446 (indicated for Stylosanthes inoculation) as positive control, besides a treatment with nitrogen (180,75mg / N per week) and a control without inoculation or nitrogen. The sowing was done in pots containing a mixture of sand and soil (1:1) autoclaved. Harvest was done 65 days after plant germination and were evaluated the nodules number and dry mass, plant dry matter and nitrogen accumulation in the dry matter. From 564 nodules, 258 isolated were purified and, with the additional 34 isolates (previously obtained), 292 isolates were consider for the study. The isolates showed high morphological diversity and were clustered in 87 groups, with threshold 70%. Most of the isolates 46% presented fast growing on YMA medium and only 0,7% were slow-growing. The authentication revealed that 44 of the 89 bacteria tested were able to form nodules in cowpea, and most of this isolates were fast-growing. This result indicated that could exist nodulation specificity between rhizobium isolates and Stylosanthes species, and diverge of the previous observations that had indicated Stylosanthes as mainly nodulated by slow-growing bacteria. Symbiotic efficiency experiment indicated that about 50% of the isolates were able to form nodules in Stylosanthes capitata similar to recommend strain and trend to higher contribution for biomass production was observed in comparison with nitrogen treatment and recommended strain as well. The strains St4A29, StG57, St1A8, StF29 and St6E2-3 have shown best performance and have potential for future researches to strains recommendation.